Desenvolvimento de sensores e instrumentação aplicados no projeto de equipamentos analisadores de qualidade de energia elétrica - Koizumi, Marcos Tsuyoshi (2012)
A poor quality power causes large losses to society. Thus it is used an equipment named power quality analyzers for magnitude measurement of these disturbances and determine the causes of these abnormality. The principal problem with these devices is the high cost and they usually are imported that invalidates multipoint measurement of client’s electrical system. In this scenario, this work aims to provide support and alternatives for the development of power quality analyzers, which consists of a set with voltage and current sensors and a central processing module. In the development of any sensors or instrumentation there are difficulties on signal conditioning generated from the used component’s electrical characteristics and principally noise. Some solutions for these problems is the use of proper measuring equipment installation, electromagnetic shielding and design of PCBs. For magnetic sensors, the hysteresis, magnetic saturation and interference by external magnetic fields introduce measurement error in the system and to solve these problems it was adopted Hall sensors in closed-loop and differential configurations. Another component that can be used is the Flux-gate sensor that has potential use in small range current measurements and offers the advantage of higher integrability in the meter system. Following is designed and built a voltage and current logger for Power quality analysis, called PQ-Logger that may utilize the sensors mentioned above. The use of a DSP and a chip for accessing a generic flash drive allows storage of these data. The PQ-Logger-Tran is other equipment that was designed to store snippets of mid-frequency transient. The results positively indicate the combined use of these current sensors and equipment developed for the measuring purpose of these parameters in a quickly and economically form in the customer‘s electrical infrastructure.